2020
DOI: 10.1002/chem.202002628
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Range LMCT Coupling in EuIII Coordination Polymers for an Effective Molecular Luminescent Thermometer**

Abstract: Ad esign for an effective molecular luminescent thermometerb ased on long-range electronic coupling in lanthanide coordination polymers is proposed. The coordination polymers are composed of lanthanide ions Eu III and Gd III ,t hree anionic ligands(hexafluoroacetylacetonate), and ac hrysene-based phosphine oxide bridges (6,12-bis(diphenylphosphoryl)chrysene). The zig-zago rientation of the single polymerc hains induces the formation of packed coordination structuresc ontaining multiple sites forC H-F intermole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The theoretical method presented is also capable to include ligand-to-metal charge transfer states (LMCT) and their interactions with other states (i.e., S 1 , T 1 , and Ln 3+ levels), treating the energy transfer rates involving the LMCT and including it in a rate equation model. [67,72,83] Thus, discernible thermal behavior in which the LMCT plays an important role in Ln 3+ -based molecular thermometers [84,85] could be also modeled.…”
Section: Theoretical and Experimental Thermometrymentioning
confidence: 99%
“…The theoretical method presented is also capable to include ligand-to-metal charge transfer states (LMCT) and their interactions with other states (i.e., S 1 , T 1 , and Ln 3+ levels), treating the energy transfer rates involving the LMCT and including it in a rate equation model. [67,72,83] Thus, discernible thermal behavior in which the LMCT plays an important role in Ln 3+ -based molecular thermometers [84,85] could be also modeled.…”
Section: Theoretical and Experimental Thermometrymentioning
confidence: 99%
“…6d ). 56 The single polymer chains show the characteristic zig-zag orientation, inducing multiple CH–F interactions, and exhibit higher thermal stability ( T d = 358 °C) than the mononuclear Eu( iii ) complex. The relative thermal sensitivity ( S m ) of the Eu( iii ) coordination polymer with chrysene linkers was higher ( S m = 2.70% K −1 at 475 K) than those of mononuclear Eu( iii ) complexes ( S m = 0.89% K −1 at 475 K).…”
Section: Photophysics Of Eu( III ) Complexes With ...mentioning
confidence: 99%
“…The LMCT bands of Eu(III) complexes with organic anion ligands such as acetylacetonate (acac), 25 trimethylheptanoate (tmh), 26−29 polycyclic aromatic hydrocarbons, 30,31 and dialkyldithiocarbamates 32,33 have been reported. Faustino reported a theoretical approach for understanding the influence of LMCT bands in lanthanide compounds and found that the energy levels of triplet and LMCT bands are important for efficient europium ion sensitization.…”
Section: ■ Introductionmentioning
confidence: 99%